The prevalence, prevention, and treatment of cardiovascular diseases in Twelve African Countries (2014–2019): An analysis of the World Health Organisation STEPwise approach to chronic disease risk factor surveillance - Wingston Felix Ng’ambi; Janne Estill; Fatma Aziza Merzouki; Cosamas Zyambo; Jonathan Chiwanda Banda; David Beran; Olivia Keiser (PLoS ONE, 2026)
Introduction Cardiovascular diseases (CVDs) are responsible for nearly a third of deaths globally. We conducted this study to understand the prevalence of history of CVDs, their prevention and treatment in twelve African countries using the World Health Organization STEPwise Approach to Surveillance (WHO STEPS) data. Methods We used secondary STEPS data extracted from 12 African countries between 2014 and 2019. CVD was defined as a self-reported history of heart attack, angina, or stroke. Weighted percentages, counts, weighted odds ratios (OR), and the corresponding 95% confidence intervals (95%CI) were computed using the R software. We fitted logistic regression models to select the predictor variables from a regression model for CVD prevalence, CVD prevention and CVD treatment binary endpoints. Results Amongst 60,294 individuals, the prevalence of CVD was 5%. The CVD prevalence was higher in older individuals, females, individuals with hypertension, smokers, people with high salt intake, and in certain countries. Eleven percent of the 23,630 individuals at high risk of CVD (≥40 years) but without a history of the disease received CVD prevention treatment. Amongst the 2,895 persons with CVDs, 22% received treatment and counselling for CVD: 34% (n = 215) receiving aspirin, 32% (n = 202) counselling for CVD risk factors, 11% (n = 66) statins, and 24% (n = 148) both statins and aspirin. The uptake of CVD treatment varied by hypertension status, sex, age and country. Conclusion The prevalence of CVD was relatively low and CVD treatment uptake was sub-optimal. Concerted efforts must be made to accelerate the diagnosis and expand treatment for CVDs in Africa if to curtail untimely deaths attributable to CVDs.